Economic impact of Covid's first wave in Mexico and Bolivia: A counterfactual perspective - Gover Barja (Journal of Local Public Economics, 2023)
The Mexican and Bolivian monthly index of global economic activity along with ARMA models are used to graph and measure the impact of the Covid pandemic shock on both economies, individually. The accumulated difference between the observed and counterfactual values show an overall -10.48% and - 12.64% loss of economic activity respectively in the 10 months from February to November 2020 of the first Covid wave, with a short-run recovery reaching 93% and 97% of their counterfactual level by November given their built-in economic forces but restrained by the pandemic.
Keywords: 330; Covid-19; Interrupted Time Series Analysis; Mexico; Bolivia